The accuracy of consensus real estate forecasts revisited. Issue 2 (2nd April 2020) - McAllister, Pat; Nase, Ilir
ABSTRACT: This study updates and expands upon the existing work on the accuracy of the IPF's Consensus Forecasts. The paper evaluates the extent to which the consensus forecasts were able to predict the relative performance. It also assesses the accuracy of implied yield forecasts and concludes that failure in yield forecasting is the main source of failure in forecasts of capital growth and total returns. A high level of agreement between the actual and forecasted sector rankings was found. Evidence of a pessimism bias was identified. Yield forecasts are consistently found to perform worst using a range of forecast performance metrics.